Expansion of Lisbon’s Docked Bike-Sharing System: Spatial and Temporal Analysis of Bike-Sharing Use in Lisbon for System Expansion - Garcia, Eva Frade (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management